PENCEHAN PENULARAN COVID19 DENGAN CARA PEMBAGIAN MASKER KEPADA PEDAGANG PASAR DI KELURAHAN GEDUNG JOHOR KECAMATAN MEDAN JOHOR KOTA MEDAN - Surya Anita; Juneris Sritonang; Cut Masyithah (JURNAL PENGABDIAN KEPADA MASYARAKAT BIDANG KESEHATAN, 2020)
Abstract Coronavirus is a large family of viruses that cause diseases ranging from mild to severe symptoms. There are at least two types of coronavirus that are known to cause diseases that can cause severe symptoms such as Middle East Respiratory Syndrome (MERS) and Severe Acute Respiratory Syndrome (SARS). Coronavirus Disease 2019 (COVID-19) is a new type of disease that has never been identified before in humans. The virus that causes COVID-19 is called Sars-CoV-2. Corona virus is zoonosis (transmitted between animals and humans). Research says that SARS is transmitted from civet cats to humans and MERS from camels to humans. Meanwhile, animals that are the source of transmission of COVID-19 are still unknown. (Ministry of Health, 2020). The use of masks is one of the preventative measures that can limit the spread of certain respiratory diseases caused by viruses, including COVID-19, masks must be used when leaving the house. (WHO, 2020).Crowded places are local transmission locations for COVID-19 transmission such as markets, the number of COVID-19 cases among market traders continues to increase with the increasing number of testing the Indonesian Traditional Market Traders Association (IKAPPI) recorded as many as 573 traders infected with COVID-19. (Tribune News, 2020). 90% of Johor market traders still continue to wear masks that have been distributed.Â Key Words : The Use, Mask, COVID-19,